Rate coefficients at 298 K and 1 atm for the tropospheric degradationof a series of C6,C7and C8biogenic unsaturated alcohols initiated by Clatoms - Gibilisco, Rodrigo Gastón (2014)
Rate coefficients for the gas-phase reactions of Cl atoms with a series of unsaturated biogenic alcohols at 298 ± 3 K and 1 atm have been measured by the relative technique in an environmental chamber with in situ FTIR detection of reactants. The rate coefficients obtained using 1-butene and isobutene as reference compounds were (in units of 10−10 cm3 molecule−1 s−1): k1((E)-2-hexen-1-ol) = (3.49 ± 0.82), k2((E)-3-hexen-1-ol) = (3.42 ± 0.79), k3 ((Z)-3-hexen-1-ol) = (2.94 ± 0.72), k4((Z)-3-hepten-1-ol) = (3.80 ± 0.86) and k5((Z)-3-octen-1-ol) = (4.13 ± 0.68). This work constitutes the first kinetic study of the reactions cited above. The rate coefficients are compared with those for other unsaturated alcohols and a correlation between the reactivity of unsaturated alcohols toward Cl atoms and the energy of the HOMO of the unsaturated alcohols is presented. Based on the obtained results, the atmospheric lifetimes of the unsaturated alcohols have been estimated and possible atmospheric implications assessed.